Depression and Associated Factors among Undergraduate Students of Private Universities in Bangladesh: A Cross-sectional Study - Mortuza Ahmmed, Md.; Ashraful Babu, Md.; Rayhan Salim, Zahir (International Journal of Psychosocial Rehabilitation, 2020)
Depression among the undergraduate students is a psychological well-being issue in the universities around the world. In Bangladesh, just one cross-sectional clear investigation was led by Sultana (2011) to address this issue which was constrained inside the medicine students. The objective of the present investigation is to recognize the elements responsible for depression among the undergraduate students in private universities in Bangladesh. For this purpose, a cross-sectional investigation based on 403 undergraduate students of International University of Business Agriculture and Technology (IUBAT) has been led from September 2019 to November 2019 employing stratified examining strategy, where every one of the class-areas has been considered as a stratum. The results of the study show that just over one-third of the students (33.7%) are depressed. Factors like skin complexion, chronic disease status, economic insolvency, ability to fulfill desire, relationship status with family members other than parents, unexpected Higher Secondary result, comfort ability within the university premise, satisfaction with the university program, ability to adjust with the continuously changing socio-cultural trends and survival status of parents have been found to have significant association with depression of the students. Besides, sociological factors like social status, social insecurity and social injustice have shown significant association with depression of the students. The findings of this study will lead future research works regarding the issue of depression among the students at various public as well as private universities in Bangladesh as there has hardly any relevant work been done so far.